(untitled) (Margalla Papers, 2021)
Humanity has been facing frequent trials in the contemporary era. One seriously emerging challenge is global warming. It has a record of disastrous impacts on earth that are severe and cataclysmic. The Intergovernmental Panel on Climate Change attributes mega-disasters to global warming. These environmental calamities have raised serious concerns for leaders, scientists, environmentalists as well as public. The defence experts warn about gradually changing weather tendencies and emerging of new security challenges. Global warming is causing continuous fluctuations in our fragile ecosystem, and any persistent malfunctioning in the ecosystem would affect the politico-economic, strategic, and even very existence of humanity. It would require rational choices and new strategic approaches for saving humanity and numerous organism species under global warming impacts. Strategists, in the future, will inevitably explore looming tactical security concerns to safeguard defence capabilities. Against this backdrop, this paper argues that global warming will create severe strategic complications. In the coming decades, traditional national defence systems will have to undergo a new transformation supportive to cope with emerging cataclysmic security issues due to global warming. Therefore, innovative lines of tactical ecological rationale will become an essential part of national defence. Bibliography Entry Shah, Syed Muhammad Ali, Shaheen Akhtar, and Fozia Bibi. 2021. "Global Warming Challenges and Tactical Ramifications: Addressing Ecological Security Concerns." Margalla Papers 25 (1): 12-22.